2021
DOI: 10.1021/acs.iecr.1c03413
|View full text |Cite
|
Sign up to set email alerts
|

K+-Doped ZnO/g-C3N4 Heterojunction: Controllable Preparation, Efficient Charge Separation, and Excellent Photocatalytic VOC Degradation Performance

Abstract: The K+-doped ZnO/g-C3N4 heterojunction had been prepared by an electrostatic attraction self-assemble method. The charge separation efficiency of the K+-doped ZnO/g-C3N4 heterojunction was 17.6 and 2.9 times those of g-C3N4 and KZO. As expected, the K ion-doped ZnO/g-C3N4 heterojunction possessed better photocatalytic isopropanol degradation performance. The highest acetone evolution rate of K+-doped ZnO/g-C3N4 heterojunction was 28.5 ppm·min–1, which was 2.7 times better than that of g-C3N4 and 1.7 times bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For ZnBVO and CN-ZnBVO-3, the deconvoluted Bi 4f spectra (Figure d) situated at 159.0 and 164.3 eV are ascribed to Bi 4f 7/2 and Bi 4f 5/2 , and characteristic peaks centered at 517.1 and 524.3 eV belong to V 2p 3/2 and V 2p 1/2 of V 5+ (Figure e) . In addition, the Zn 2p spectra (Figure f) presents two prominent peaks positioned at 1021.1 and 1044.4 eV severally referring to Zn 2p 3/2 and Zn 2p 1/2 , in which the spin–orbit splitting of Zn 2p was 23.3 eV, manifesting that the existence of Zn 2+ in the CN-ZnBVO-3 . Notably, due to the M–O–C strong interaction in heterojunction, the V 2p and Zn 2p peaks of CN-ZnBVO-3 are slightly shifted in comparison with single ZnBVO (Figure e and f), indicating the redistribution of electrons in CN-ZnBVO-3 interface, which is beneficial to accelerating the interfacial charge separation kinetics, thus promoting photocatalytic CO 2 reduction.…”
Section: Resultsmentioning
confidence: 95%
“…For ZnBVO and CN-ZnBVO-3, the deconvoluted Bi 4f spectra (Figure d) situated at 159.0 and 164.3 eV are ascribed to Bi 4f 7/2 and Bi 4f 5/2 , and characteristic peaks centered at 517.1 and 524.3 eV belong to V 2p 3/2 and V 2p 1/2 of V 5+ (Figure e) . In addition, the Zn 2p spectra (Figure f) presents two prominent peaks positioned at 1021.1 and 1044.4 eV severally referring to Zn 2p 3/2 and Zn 2p 1/2 , in which the spin–orbit splitting of Zn 2p was 23.3 eV, manifesting that the existence of Zn 2+ in the CN-ZnBVO-3 . Notably, due to the M–O–C strong interaction in heterojunction, the V 2p and Zn 2p peaks of CN-ZnBVO-3 are slightly shifted in comparison with single ZnBVO (Figure e and f), indicating the redistribution of electrons in CN-ZnBVO-3 interface, which is beneficial to accelerating the interfacial charge separation kinetics, thus promoting photocatalytic CO 2 reduction.…”
Section: Resultsmentioning
confidence: 95%
“…[26] The K-doping resulted in a crossed energy band structure, which can make excellent the separation of carriers, and the higher specific surface area and mesoporous structure could improve the reactant mass transfer efficiency for rapid surface reactions. [57] The energy band position of noble metals is lower than the CB position of graphitic phase carbon nitride semiconductors, so that photoexcited electrons can be captured by the surface noble metal, achieving electron-hole separation and extending its light-sensitive region to the visible region. [58] The Surface Plasmon Resonance (SPR) induced by metallic nanoparticles also plays a key role in improving light absorption and carrier separation.…”
Section: Classification Of Doping G-c 3 Nmentioning
confidence: 99%
“…A growing body of research indicates that composite material photocatalysts outperform their single-component counterparts in terms of photocatalytic activity. For instance, Liu et al synthesized ZnO/g-C 3 N 4 nanocomposites that exhibited superior activity in H 2 O 2 production [31], while Wang et al TiO 2 /ZnIn 2 S 4 photocatalyst demonstrated commendable activity in CO 2 reduction [32]. Similarly, the TiO 2 /Fe 2 O 3 composite engineered by Mirmasoomi et al exhibited remarkable activity in photocatalytic pesticide degradation [33].…”
Section: Introductionmentioning
confidence: 99%